A 15-year survey of pollen aeroallergens in North Texas - Howard C. Crisp, MD; Meredith P. Richards, PhD (Journal of Allergy and Clinical Immunology: Global)
Background: Knowledge of airborne pollen seasons is essential for physicians to accurately diagnose and treat patients with allergic respiratory diseases. Although the Dallas-Fort Worth metropolitan area in North Texas is home to more than 8 million residents, it lacks a published pollen calendar. Objective: Our objectives were 3-fold: (1) determine the most common allergenic pollens in North Texas and when they are present, (2) identify how pollen concentrations have changed over time, and (3) assess how weather affects the daily pollen concentrations. Methods: We obtained 15 years of daily pollen concentration and weather data for North Texas. Data were analyzed in R by using the AeRobiology package. The AeRobiology package was used to interpolate missing data, create heatmaps of daily pollen concentrations, and calculate the pollen seasons. We use regressions accounting for seasonal effects to determine changes over time and the effect of weather factors. Results: In North Texas, pollen is present throughout the year. Spring-dominant Quercus and winter-dominant Juniperus constitute more than half of the total annual pollen production. Ulmus and Ambrosia make up the bulk of the fall pollen. Consistent with climate change, daily pollen concentrations have been increasing over time. Moreover, higher pollen concentrations are associated with higher maximum daily temperature and average daily wind speed. Conclusions: These pollen calendars will help physicians in the region care for patients with allergic respiratory disease, who may present with more severe disease as pollen concentrations are increasing over time.